222Rn as Natural Tracer for LNAPL Recovery in a Crude Oil‐Contaminated Aquifer. Issue 2 (27th January 2015) - Ponsin, Violaine; Chablais, Amélie; Dumont, Julien; Radakovitch, Olivier; Höhener, Patrick
Abstract The objective of this study was to investigate whether 222Rn in groundwater can be used as a tracer for light non‐aqueous phase liquid (LNAPL) quantification at a field site treated by dual‐phase LNAPL removal. After the break of a pipeline, 5 ha of soil in the nature reserve Coussouls de Crau in southern France was contaminated by 5100 m3 of crude oil. Part of this oil seeped into the underlying gravel aquifer and formed a floating oil body of about 3.9 ha. The remediation consists of plume management by hydraulic groundwater barriers and LNAPL extraction in the source zone. 222Rn measurements were performed in 21 wells in and outside the source zone during 15 months. In uncontaminated groundwater, the radon activity was relatively constant and remained always >11 Bq/L. The variability of radon activity measurements in wells affected by the pump‐and‐skim system was consistent with the measurements in wells that were not impacted by the system. The mean activities in wells in the source zone were, in general, significantly lower than in wells upgradient of the source zone, owing to partitioning of 222Rn into the oil phase. The lowest activities were found in zones with high non‐aqueous phase liquid (NAPL) recovery. LNAPL saturations around each recovery well were furthermore calculated during a period of high groundwater level, using a laboratory‐determined crude oil–water partitioning coefficient of 38.5 ± 2.9. This yielded an estimated volume of residual crude oil of 309 ± 93 m3 below the capillary fringe. We find that 222Rn is a useful and cheap groundwater tracer for finding zones of good LNAPL recovery in an aquifer treated by dual‐phase LNAPL removal, but that quantification of NAPL saturation using Rn is highly uncertain.